Effect of progesterone supplementation on conception rate following single and double insemination in repeat breeder cows - Kumar, Pravesh; Singh, Madhumeet; Kumar, Navneet; Kumar, Amit (The Indian Journal of Animal Sciences, 2012)
Repeat breeder cows (141) were used to study the effect of progesterone supplementation on conception rate following single and double insemination in repeat breeder cows. In treatment group cows 500 mg hydroxyprogestrone caproate was injected intramuscularly and no treatment was given in control group cows. The animals included in progesterone treatment group were divided into 3 groups, viz. the progesterone administration simultaneous to AI (group 1, n=30), conception was 18.18% with single insemination and 21.05% with double insemination. In group 2, (n=32), progesterone was administered day 3 post AI, the conception was 46.05 and 47.36% with single and double insemination respectively. Whereas in group 3 (n=44), administration of progesterone on fifth day post AI, the conception was 45.45 and 48.48% with single and double insemination respectively. In control group (n=35), when no treatment was given, the conception was 18.75 and 31.57% with single and double insemination, respectively.